Chinese Versus United States Workplace Ageism as GATE-ism: Generation, Age, Tenure, Experience - North, Michael S. (Frontiers in Psychology, 2022)
Ageism is a pan-cultural problem, and correspondingly, increased research attention worldwide has focused on how a person’s age drives prejudice against them. Nevertheless, recent work argues that chronological age alone is a limited predictor of prejudice—particularly in the workplace, where age conflates intertwined elements (e.g., life stage and work experience), and across cultures, in which the nature of ageism can substantially differ. A recent organizational behavior (GATE) framework advocates for extending beyond numerical age alone, focusing instead on prejudice arising from workers’ perceived Generation (birth cohort), Age (life stage), Tenure (time with organization), and Experience (accumulated skillset over time). In addition to clarifying the multifaceted nature of workplace ageism, GATE helps uncover potential cultural ageism differences. Using the United States and China as focal Western and Eastern prototypes, the current paper compares Eastern and Western cultures through a GATE Lens. Eastern and Western cultures adopt different perceptions of generations (e.g., United States “Boomers,” versus Chinese “Cultural Revolution” generation), elder life stages (United States warm-but-incompetent older adults, versus Eastern pragmatic elder resource concerns), organizational tenure expectations (Western job-hopping, versus Eastern filial-piety-based loyalty), and desired experience levels (shaped different by higher Eastern frequency of mandatory retirement practices and family business ventures). Moreover, existing research offers clues for how workplace GATE-ism likely differs between cultures, but more research is needed. Future research should adopt a nuanced GATE conception of “age”-ism, toward enhanced ageism understanding and the ability to utilize a globally aging workforce.